INFLUENCING THE PURCHASE PATH: EXPLORING SOCIAL MEDIA INFLUENCER’S ROLE IN E-COMMERCE CONSUMER DECISION MAKING - Arya, Aman; Goel, Pooja; Verma, Subhash Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rise of social media influencers (SMIs) has significantly transformed e-commerce marketing, particularly between 2019 and 2024. As digital platforms became central to consumer behavior, SMIs emerged as crucial players in shaping purchasing decisions through personalized and authentic engagement. This study explores the role of SMIs in influencing the e-commerce consumer decision- making process, focusing on brand awareness, product consideration, purchasing, and post-purchase engagement. The research delves into the varying impacts of macro-, micro-, and nano-influencers across different product categories, supported by quantitative and qualitative data from surveys, focus groups, and social media analytics. Key findings indicate that SMIs, particularly micro- and nano-influencers, have outperformed traditional marketing channels in building trust and driving consumer engagement. The study also highlights emerging trends such as the integration of artificial intelligence in influencer marketing and the growing importance of transparency and authenticity. Ethical concerns, particularly around disclosure and fake engagement, are discussed, alongside the challenges of measuring return on investment (ROI) in influencer campaigns. This research contributes to a deeper understanding of the strategic importance of influencer marketing in e-commerce, providing actionable insights for brands looking to optimize their digital marketing strategies. As the industry evolves, the findings underscore the need for brands to adapt to emerging trends and ethical standards to maintain the effectiveness and credibility of their influencer partnerships.